Ciliwung Ecoriparian Tourism Destination Concept for Increasing Local Community Income - Setyawati, Irma; Nugraha, Rizki Nurul (Westscience Press, 2023)
In an effort to restore environmental sustainability and the socio- economic needs of the community, as a natural ecology, the riverbank area is a natural area that must be protected, with the benefit of being a tourist destination, which can attract visitors, to realize the preservation of the natural environment, and increase the per capita income of the community Around the riverside area (ecoriparia ), it is necessary to plan appropriate natural tourism destinations. To make this plan, of course, requires high intellectuals but still maintains the relationship between humans and their gods, so that the development and development of the area is carried out without reducing the meaning of environmental interests, where the interests of nature conservation become commercial areas. For this reason, an in-depth analysis is needed to make the